Anti-Food allergic activity of sulfated polysaccharide from Gracilaria lemaneiformisis dependent in immunosuppression and inhibition of p38 MAPK - Liu, Qing-Mei; Yang, Yang; Maleki, Soheila J.; Alcocer, Marcos; Xu, Sha-Sha; Shi, Chao-Lan; Cao, Min-Jie; Liu, Guang-Ming (American Chemical Society, 2016)
Polysaccharides from Gracilaria lemaneiformis in particular possess various bioactive functions, but their antiallergic activity remains incompletely defined. Sulfated polysaccharide from Gracilaria lemaneiformis (GLSP) was obtained by water extraction and ethanol precipitation followed by column chromatography. BALB/c mice, RBL-2H3, and KU812 cells were used for verifying the anti food allergic activity of GLSP. According to the results of mice experiment, GLSP was able to alleviate allergy symptoms, to reduce TM-specific IgE and IgG1, to suppress Th2 cell polarization, and to promote the function of regulatory T (Treg) cells. In addition, GLSP had the ability to inhibit the function of RBL-2H3 cells. Furthermore, GLSP inhibited the activation of KU812 via suppression of p38 mitogen-activated protein kinase (MAPK). In conclusion, immunosuppression as well as the reduction in the level of p38 MAPK may contribute to GLSP’s putative activity against food allergy. GLSP may be used as a functional food component for allergic patients.